The effect of some organizational variables on health and occupa-tional accidents. - López-Araújo, Blanca; Osca Segovia, Amparo (Anales de Psicología / Annals of Psychology, 2010)
Construction work is a very dangerous occupation, thus it is important to reduce worker exposure to organizational stressors. This study examines the relationships between three organizational variables (job stress, safety climate, social support) and accidents or near-miss out-comes. Self-reported questionnaire data collected from 285 construction workers and were analysed using structural equation modelling. One theo-retical model was tested where organizational variables could be related through the mediating effects of physical or psychological symptoms. Job stress, safety climate and social support were found to be indirectly related to accidents through psychological and physical symptoms. However, there was no support for the near misses model. Implications for health and safety on construction sites are discussed.